Parental Socioeconomic Status and Weight Faltering in Infants in Japan - Kachi, Yuko; Fujiwara, Takeo; Yamaoka, Yui; Kato, Tsuguhiko (Frontiers in Pediatrics, 2018)
Background Previous studies in the UK and Denmark found no significant association between low socioeconomic status (SES) and weight faltering. However, to our knowledge, there are no studies from other developed countries. We examined the association between parental SES and weight faltering in infants up to 1.5 years of age, and investigated whether the inequalities changed between 2001 and 2010 in Japan. Methods We used data from two Japanese population-based birth cohorts started in 2001 (n=34,594) and 2010 (n=21,189). Parental SES was assessed as household income and parental education when the infant was 6 months old. Weight faltering was defined as the slowest weight gaining in 5% of all children in each cohort. Logistic regression analyses were conducted with adjustment for covariates. The relative index of inequality was used to assess relative impact of parental SES on weight faltering. Results Infants in the lowest quartile of household income were 1.29 (95% confidence interval [CI]: 1.10,1.52) and 1.27 (95% CI: 1.03,1.56) times more likely to experience weight faltering than those in the highest income quartile both in the 2001 and 2010 cohorts, respectively. The relative index of inequality for household income was 1.66 (95% CI: 1.36,1.96) in 2001 and 1.86 (95% CI: 1.42,2.31) in 2010. Conclusions Infants from lower income families have a greater risk of weight faltering in Japan. Additionally, the income-related inequalities in weight faltering did not change between the two cohorts. Social policies to address maldistribution of weight faltering due to household income are needed.